PELATIHAN AKUNTANSI DENGAN TOPIK OBLIGASI KEPADA MURID SMA KRISTEN YUSUF, JAKARTA - Nastasya Cindy Hidajat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
This Community Service Activity (PKM) is one of the manifestations of the Tri Dharma of Higher Education, to provide benefits to the community. The target of this PKM is training on bonds and accounting for students of SMA Kristen Yusuf, Jakarta. It is hoped that this training activity can provide benefits for Kristen Yusuf High School students to have better understanding of bonds and their accounting treatment so that they can help them prepare for accounting competitions and as an introduction when entering college later. In addition, it is also hoped that this training will provide benefits for Tarumanagara University, especially the Faculty of Economics and Business, in fostering good relations with schools so as to get a better reputation from schools and students. This training is given to students of class XI and XII. The training is carried out every Wednesday during November 2021 through the Zoom application with a total of 4 sessions with a duration of 45 minutes per each session. The implementation of the activities included the presentation of material by the Untar PKM Team, then continued with practice questions and ended with a question and answer session. During the implementation, it was seen that the students enthusiastically welcomed this training activity. The results of the questionnaire also show that the material presented can increase students' knowledge and increase their interest in the accounting field, and hope to return to training on a different topic.